Verbal Communication Symbols of the Wives of Navy Personnel within The Indonesian National Army - et. al, Dina Kristina, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
When a woman marries a marine from The Naval Branch (Angkatan Laut – abbrev AL) of The Indonesian National Army (Tentara Nasional Indonesia - TNI) she is automatically included in an organization callled Jalasenastri. Jalasenastri is a social organization aimed at providing welfare for Navy Personnel and their families. As an organization Jalasenastri has not only developed to be a collective but also to be a form of identity for its members. This has not only come about based on the physical attributes of the members but also from the verbal interaction that has become part and parcel of their identity as members. This research was made to find out how this verbal communication has become an ethical symbol for the wives of sailors in The Indonesian National Army. The metodology used in this research is a qualatative method with a symbolic interaction theory. The subjects of this research were the Korcab 3 Jalasenastri and CBS Puspomal members in Jakarta. The results of this research indicate that the verbal codes used within Jalasenastri are hierachial and collective in nature. The verbal codes of the Jalasenastri are used as a form of speech for showing respect, esteem and politeness. The hierachial concept which is indiretly applied is one of the representation of the rank or seniority of individual Navy Servicemen.